Analisis Tingkat Kecemasan Dalam Pembuatan Karya Tulis Ilmiah Mahasiswa UPI di Kampus Purwakarta (Current Research in Education: Conference Series Journal, 2023)
The 4C competence has been recognized by many experts as one of obligatory student learning outcomes, including students of Kampus UPI di Purwakarta. Therefore, student learning activity, whether in-class or out-class, should be directed toward mastery of those competences. One of many attempts that has been done was an assignment to create a scientific writing, in this case are Program Kreativitas Mahasiswa (PKM) proposals. However, there is a problem based on the amount of those proposals that have been rejected by the PKM Committee. This was an alarming problem and needed to be analyzed and solved as soon as possible. This study is done by a descriptive analytical method with a qualitative approach. The number of respondents was 94 students from UPI at the Purwakarta Campus. The number of respondents are 94 students from PSTI Kampus UPI di Purwakarta. The results of this study show that 70.4% of participants state they only had extrinsic motivation, 54.9% dislike scientific writing activity or task, and 51% admit that they had trouble finding journal references. We conclude that the students of Kampus UPI di Purwakarta still have yet to master references search technique. It affects their motivation and hinder their progress to achieve the intended learning outcome. Furthermore, we determine that it could be solved by introducing a search application in order to ease anxiety and improve the quality of their Scientific Writing.